The Reflection of Psychological Influence of Hamidian Massacares in Arpiar Arpiaryan's Novelette "The Crimson Offering" - Sargsyan, Nara (History and Culture, 2021)
The article focuses on the psychological influence of the Hamidian massacres occurred in 1894-1896 and its political motives in A. Arpiaryan's novel "The Crimson Offering". It was noticed that in 1894-1896 due to the first genocide, the problem of a new type of literary character, who underwent mental and psychological trauma has not been examined. Hence, in the novel “The Crimson Offering” A. Arpiaryan created such personages, which were reflected as two complementary, but antithetical characters in the face of Ter Husik and Hayrapet Efendi.